Salinity-dependent nitrifier adaptation shapes partial nitritation resilience under dynamic saline conditions: Mechanistic insights into Nitrosomonas salt adaptation - Yunjing Wang; Cong Wang; Xiaoyu Han; Jiayuan Ji; Jian Song; Mingming Zhang; Weikang Qi; Yongzhen Peng (Water Research, 2026)

Millennial-scale erosion patterns unveil a mid-crustal ramp in the main Himalayan thrust: Implications for tectonic-climatic-erosion coupling - Xuemei Li; Weiming Liu; Huiping Zhang; Mingming Han; Chaohua Wu; Luqiang Tang (Geomorphology, 2026)

Macro-meso failure mechanism and meso-scale evolution law of aeolian sand under engineering low-velocity impact - Xuekai Han; Yingchun Qi; Yuqiong Li; Jianzhong Zhu; Heshu Huang; Shiyi Zhu; Jiangquan Li; Mingming Dong; Meng Zou; Lianbin He (Soil Dynamics and Earthquake Engineering, 2026)

Identification of the 1870 M7¼ Batang earthquake surface rupture and its implications for tectonic transformation in the southeastern Tibetan Plateau - Yanbao Li; Lichun Chen; Feng Luo; Shihai Wang; Shuaipo Gao; Mingming Han; Lili Lu; Mingwen Yang (Global and Planetary Change, 2026)

Process intensification of directed fine-particle transport by synthetic-jet-generated vortex rings: Experimental and numerical investigation - Mingming Chai; Jiaqi Ran; Hailin Gu; Huan Han (Chemical Engineering Journal, 2026)

Anthropogenic or climate-driven? Mechanisms of the AD 1642 extreme flood Disaster of the Yellow River in Ancient Kaifeng, China - Junjie Shen; Aishan Han; Panpan Chen; Junwei Wan; Mengdie Zhao; Mingming Jia; Yan Tian; Peng Zhang; Huayong Li; Qianyu Tang; Peng Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Inactivation of Staphylococcus aureus on eggshells by combined slightly acidic electrolyzed water and UV: Influence factors, mechanistic insights, and penetration risk evaluation - Yitian Zang; Yao Zang; Yingjie Feng; Mingming Tu; Haojie Zhu; Jiahong Han; Shan Bing; Yanjiao Li; Xianghui Zhao; Nengshui Ding; Guoyun Wu (Food Control, 2026)

Synergistic electrocatalytic reduction-oxidation cascade for efficient degradation of triclosan over an optimal amino-ionic liquid functionalized CoNi/RGO cathode - Dandan Xu; Xueli Xie; Han Zhou; Qin Zhang; Yanan Zhang; Min Huang; Yijian Zhong; Mingming Fu; Shaoyuan Bai (Environmental Research, 2026)

Transformation characteristics and mechanisms of phosphorus during supercritical water gasification of pig manure - Mingming Du; Jing Gu; Haoran Yuan; Yunan Chen; Jingkun Han; Jiaxin Liao (Biomass and Bioenergy, 2026)

Measuring the impact of urban morphology on residential energy consumption at the neighborhood-level in the Netherlands - Han Yu; Mingming Hu; Arnold Tukker; Peter Berrill (Sustainable Cities and Society, 2026)

Gill dysfunction and metabolic disruption: the size-dependent effects of microplastics on Chiromantes haematocheir - Yijuin Tay; Ji Liang; Yuanhao Yang; Di Ren; Xingkong Ma; Mengyu Bao; Zihan Zhou; Mingming Han; ZhenChao Li; Anisah Lee Binti Abdullah; Tianheng Gao; Qichen Jiang (Marine Environmental Research, 2026)

Simultaneous leaching of Li, Rb, Cs from lepidolite via external electric field enhanced alkali leaching - Kun Xu; Mingming Yu; Heyue Niu; Yusufujiang Mubula; Zhehan Zhu; Di Han; Jingzhong Kuang; Lingguo Meng; Guichun He (Minerals Engineering, 2026)

Particle Type- and Morphology-Associated Neurotoxicity of Microplastics and Nanoplastics via Divergent PPARγ Modulation in Zebrafish - Chenchen Han; Lixia Peng; Xinlei Guo; Yaqi Yu; Mingming Niu; Willie J.G.M. Peijnenburg; Zhiqiang Li; Xilin She; Chuanhong Wu; Lianzhen Li (Journal of Hazardous Materials, 2026)

Temporal trajectory and determinants of permanent gully erosion in the grassland: A long-term analysis spanning 1973–2020 - Zhicai Xiao; Mingming Guo; Xin Liu; Zhuoxin Chen; Xingyi Zhang; Jinzhong Xu; Shaoliang Zhang; Jielin Liu; Xing Han; Ruifeng Xie (Soil and Tillage Research, 2026)

Fracture evolution and mechanical response of coal with damage induced by oil-gas seepage - Yawu Shao; Wei Yao; Lei Zhu; Gang Han; Haifei Lin; Hu Liu; Jiahao Xie; Mingming Sun; Jin Wang (Bulletin of Engineering Geology and the Environment, 2026)

Mapping coastal aquaculture ponds in China without dependence on water levels: New insights from pond dikes derived from Sentinel-1/2 imagery - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Quan Han; Chunying Ren; Zongming Wang (Environmental Impact Assessment Review, 2026)

From Adaptation to Collapse: Immune Remodeling, Mitochondrial Dysfunction, and Cell Death Induced by Polystyrene Nanoplastics in Procambarus clarkii Hepatopancreas - Shengyan Pu; Han Mingming; Yi Juin Tay; Xiao Qing; Fu Hongmei; Wang Yiting; Li Zhenchao; Zhang Jingyou; Anisah Lee Binti Abdullah; Ji Liang (Marine Biotechnology, 2026)

Visible-light activation of H2O2 by red-mud/biochar: 1O2 pathway for efficient tetracycline degradation - Yi Han; Ting Shi; Shuai Yang; Mingming Wu; Hongcheng Gao; Dejin Wang; Emeka E. Oguzie; Changyong Zhang (ENGINEERING Environment, 2026)

Synergistic acceleration of woody debris decomposition by nitrogen deposition and mycorrhizal network disruption in a temperate forest - Zhongjie Sun; Yaxuan Cui; Zixuan Wang; Yipu Wu; Yaru Nie; Mingming Cui; Zahoor ul Haq; Mohsin Khan; Shijie Han; Feirong Ren; Junqiang Zheng (Applied Soil Ecology, 2026)

Fine-scale aboveground biomass estimation of restored vegetation in tailings ponds: integrating UAV multi-source data and explainable machine learning - Xiaojie Chi; Mingming Jia; Jingjing Zhao; Fuping Li; Chunyan Lu; Yongbin Zhang; Dongyun Han; Xiaohui Hu; Xiaoguang Li; Guie Tian; Mingyue Liu; Weidong Man (Computers and Electronics in Agriculture, 2026)

Development characteristic of permanent gully morphology at the small watershed scale and its relations with driving factors along the Mollisols Belt of Northeast China - Xiaohui Lian; Ningning Xiao; Mingming Guo; Xingyi Zhang; Xin Liu; Jinzhong Xu; Shengmin Zhang; Xing Han (Soil and Tillage Research, 2026)

Toxic effects of tire wear particle leachate on benthic fish Misgurnus anguillicaudatus: An integrated assessment of immunosuppression, metabolic disruption, and microbiome dysbiosis across concentration gradients - Hao Liu; Ji Liang; Xue Du; Yiming Lee; Anisah Lee Binti Abdullah; Yi Juin Tay; Mingming Han (Environmental Pollution, 2026)

Permeability Evolution and Failure Behavior of Coal Under Coupled Oil–Gas Porous Flow and Mining-Induced Stress - Yawu Shao; Lei Zhu; Gang Han; Haifei Lin; Wei Yao; Hu Liu; Jiahao Xie; Tao You; Mingming Sun; Jin Wang (Rock Mechanics and Rock Engineering, 2026)

Characterizing China’s post-overbuilding era: cement industry prospects from 2025 to 2100 - Han Tu; Shoujuan Tang; Guangxin Liu; Yang Li; Mingming Hu; Arnold Tukker; Yuping Yan; Lei Shi (Resources, Conservation and Recycling, 2026)

Boron-doped diamond electrodes for environmental applications: From structure-property relationships to electrochemical remediation and sensing - Liwei Chen; Yurong Guo; Yanrong Chen; Yan Zhang; Mingming Gao; Yingying Jing; Yen Leng Pak; Xing Gao; Suqin Han; Lan Bao; Jibin Song (Journal of Environmental Chemical Engineering, 2026)

Antifungal activity of Lactobacillus sakei PLL12 and Lactococcus lactis PLL15 against Aspergillus niger and their application in bread preservation - Jinghan Zhang; Zhenlin Han; Mingming Huang; Xinyu Li; Qianyu Li; Zunyang Song; Jingying Shi (Food Control, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Transcriptome analysis reveals the response mechanism of largemouth bass (Micropterus salmoides) brain to MSRV infection - Qi Guo; Pengfei Wang; Bao Lou; Weifeng Shen; Mingming Han; Wenzhi Guan; Sunjian Lyu; Li Liu (Fish & Shellfish Immunology, 2026)

High entropy sulfides enable atomic-level interactions for high-performance rechargeable aluminum batteries - Wenpeng Cao; Kai Du; Changzhan Li; Pengcheng Liu; Mingming Xie; Fangyan Cui; Chunhao Sun; Mingshan Han; Jinshu Wang; Yuxiang Hu (Chemical Engineering Journal, 2026)

An integrated insight into damage behaviors of induced cracks based on fractal characteristics - Han Cao; Peimei Liu; Mingming Zheng; Weiping Tang; Lichang Wang; Habiyakare Erneste (Bulletin of Engineering Geology and the Environment, 2026)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Generation of reactive nitrogen species for ultrasound-catalyzed tumor treatment through cascade reaction by self-supplied H2O2 nano-reactor - Hao Wu; Zhiping Zhang; Zhao Wang; Lei Yu; Quanxiang Han; Yurong Guo; Mingming Gao; Yingying Jing; Liwei Chen; Xing Gao; Yen Leng Pak; Jibin Song (Chemical Engineering Journal, 2025)

The scientific basis for addressing marine micro- and nanoplastic pollution: Informing effective monitoring and remediation frameworks - Weiwei Huang; Wenzong Zhou; Yi juin Tay; Ji Liang; Zihan Zhou; Mingming Han; Chenxi Zhu; Jingyou Zhang; Yiming Li; Qichen Jiang; Weiwei Lv (Aquatic Toxicology, 2025)

Microbially induced calcium carbonate precipitation (MICP) reduces sandbank dust emission during flood recession process - Mingming Cui; Hao Liu; Jing Wang; Biqi Bao; Zhiguang Han; Junqiang Zheng (Journal of Soils and Sediments, 2025)

Enhanced Pickering interfacial biocatalysis in phosphatidylserine synthesis via phospholipase D immobilization with optimized bifunctional strategy - Huihui Liu; Yihan Liu; Zhongmu Han; Yufei Zhang; Mingming Zheng (Food Chemistry, 2025)

Response mechanisms of nitrogen-cycling microbiota and metabolic functions to nitrogen input in the Panax ginseng rhizosphere - Kexin Li; Mei Han; Mingming Wan; Limin Yang (Plant and Soil, 2025)

Direct ammonia oxidation colony-driven DAAO process: construction strategy and optimization of denitrification efficacy - Yuwei Mi; Dingqiu Wei; Shuangjiang Liu; Defeng Li; Han Chen; Yijie Zheng; Mingming Chen; Dongru Qiu; Renbing Bao; Jian Xu; Zhiquan Hu (Chemical Engineering Journal, 2025)

Unraveling the stress response: How low temperature and nanoparticles impact the chinese mitten crab (Eriocheir sinensis) - Zihan Zhou; Jian Tian; Qin Si; Yi Juin Tay; Mingming Han; Qichen Jiang; Lanmei Wang (Journal of Hazardous Materials, 2025)

Integrated Transcriptomic Analysis Uncovers the Protective Effects of Berberine Hydrochloride in Enhancing Hepatic Caecum Response of Branchiostoma belcheri (Chinese lancelet) to Aeromonas hydrophila - Yi Juin Tay; Ji Liang; Shu Yao; Mingming Han (Marine Biotechnology, 2025)

Antifungal activity of 2-decanone against Monilinia fructicola and its application in combination with boscalid in mitigating brown rot disease in peach fruit - Xiaorui Wang; Mingming Huang; Wenhui Li; Yingying Shi; Yinuo Tang; Han Zhang; Bin Wu; Zheng Zhang; Zunyang Song; Jingying Shi (Physiological and Molecular Plant Pathology, 2025)

In-situ synergistic effect of CO2 cycloaddition reactions over bifunctional Ce-SBA-15/NH3I heterogeneous catalysts without co-catalysts: A combination of kinetic and theoretical research - Sai Geng; Shiyuan Niu; Mingming Han; Fuhua Zhang; Zhaofei Wang; Anyang Shi; Songtao Wang; Bolin Zhao; Jingyi Lao; Jialuo Yin; Yue Liu; Huihui Wang; et al. (Chemical Engineering Journal, 2025)

Associations between long-term exposure to ultrafine particles and type 2 diabetes: A large-scale, multicenter study in China - Tingting Yang; Yi Guo; Renhua Zhang; Jianqin Zhong; Zixuan Xu; Leilei Liu; Ziwei Peng; Fuchao Wang; Yixuan Jiang; Yixiang Zhu; Qiaolan Liu; Yunyun Wu; et al. (Journal of Hazardous Materials, 2025)

Physicochemical and functional properties of two kinds of Schisandra proteins and their antioxidant activity in H2O2-treated HepG2 cells - Haidong Wang; Han Zhang; Hongyan Zhou; Lingkun Meng; Hongyin Zhang; Chunguang Yi; Guangzhe Li; Mingming Yan (Food Research International, 2025)

Evaluation of six latest precipitation datasets for extreme precipitation estimates and hydrological application across various climate regions in China - Yongjing Wan; Daiyuan Li; Jingjing Sun; Mingming Wang; Han Liu (Atmospheric Research, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

The potential of rooftop photovoltaics to meet Dutch residential electricity demand under heat transition scenarios - Xining Yang; Han Wang; Mingming Hu; Zhi Cao; Chunbo Zhang; Xiaoyang Zhong (Journal of Cleaner Production, 2025)

Long-term PS micro/nano-plastic exposure: Particle size effects on hepatopancreas injury in Parasesarma pictum - Ji Liang; Anisah Lee Binti Abdullah; Yiming Li; Hong Wang; Sen Xiong; Mingming Han (Science of The Total Environment, 2024)

Integrin A5B1-mediated endocytosis of polystyrene nanoplastics: Implications for human lung disease and therapeutic targets - Mingming Han; Ji Liang; Kai Wang; Qin Si; Chenxi Zhu; Yunlong Zhao; Nurzalina Abdul Karim Khan; Anisah Lee Binti Abdullah; Aileen Tan Shau-Hwai; Yi Ming Li; Zihan Zhou; Chunqi Jiang; et al. (Science of The Total Environment, 2024)

Amygdala-Targeted Relief of Neuropathic Pain: Efficacy of Repetitive Transcranial Magnetic Stimulation in NLRP3 Pathway Suppression - Zhenhua Zhang; Zixin Hou; Mingming Han; Peng Guo; Kemin Chen; Jie Qin; Yuanzhang Tang; Fengrui Yang (Molecular Neurobiology, 2024)
This study investigates the effectiveness of repetitive transcranial magnetic stimulation (rTMS) as a nonpharmacological approach to treating neuropathic pain (NP), a major challenge in clinical research. Conducted on male Sprague-Dawley rats with NP induced through chronic constriction injury of the sciatic nerve, the research assessed pain behaviors and the impact of rTMS on molecular interactions within the amygdala. Through a comprehensive analysis involving Mechanical Withdrawal Threshold (MWT), Thermal Withdrawal Latency (TWL), RNA transcriptome sequencing, RT-qPCR, Western blotting, immunofluorescence staining, and Co-Immunoprecipitation (Co-IP), the study focused on the expression and interaction of integrin αvβ3 and its receptor P2X7R. Findings reveal that rTMS significantly influences the expression of integrin αvβ3 in NP models, suggesting an inhibition of the NP-associated NLRP3 inflammatory pathway through the disruption of integrin αvβ3-P2X7R interactions. These outcomes highlight the potential of rTMS in alleviating NP by targeting molecular interactions within the amygdala, offering a promising therapeutic avenue for managing NP.

Multi-omics reveals the particle size effect of nanoplastics on the hepatopancreas and intestinal toxicity of crustacean model Neospoda palmata - Mingming Han; Tian Zhu; Zihan Zhou; Yiming Li; Cigang Yu; Ji Liang; Hong Wang; Qin Si; Qichen Jiang (Science of The Total Environment, 2024)

Construction of bienzyme-inorganic hybrid nanoflowers as a high-efficiency biocatalyst for the degradation of indole - Jiping Han; Qiang Zhang; Ke Zhang; Ying Liu; Deyu Rao; Yaohua Gu; Mingming Li; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Polystyrene microplastics induce molecular toxicity in Simocephalus vetulus: A transcriptome and intestinal microorganism analysis - Chenxi Zhu; Hui Zhou; Mengyu Bao; Shengkai Tang; Xiankun Gu; Mingming Han; Peng Li; Qichen Jiang (Aquatic Toxicology, 2024)

Quercetin alleviates kidney damage caused by mercury Chloride: The protective effects of quercetin on autophagy and inflammation were studied based on TRIM32/TLR4/LC3 pathway - Fan Jin; JiaYue Li; Chenyu Zhao; Lixiang Gu; Min Pu; Simin Jiang; Mingming Liang; Ying Zhao; Jianli Shen; Agabuwei Agabuwei; Qin Han; Dan Liao (Toxicon, 2024)

Micro/nano-plastics impacts in cardiovascular systems across species - Ji Liang; Feng Ji; Anisah Lee Binti Abdullah; Wei Qin; Tian Zhu; Yi Juin Tay; Yiming Li; Mingming Han (Science of The Total Environment, 2024)

Gain-of-function variants in GSDME cause pyroptosis and apoptosis associated with post-lingual hearing loss - Yun Xiao; Lei Chen; Kaifan Xu; Meijuan Zhou; Yuechen Han; Jianfen Luo; Yu Ai; Mingming Wang; Yu Jin; Ruifeng Qiao; Shuhui Kong; Zhaomin Fan; et al. (Human Genetics, 2024)
Gasdermin E (GSDME), a member of the gasdermin protein family, is associated with post-lingual hearing loss. All GSDME pathogenic mutations lead to skipping exon 8; however, the molecular mechanisms underlying hearing loss caused by GSDME mutants remain unclear. GSDME was recently identified as one of the mediators of programmed cell death, including apoptosis and pyroptosis. Therefore, in this study, we injected mice with GSDME mutant (MT) and examined the expression levels to assess its effect on hearing impairment. We observed loss of hair cells in the organ of Corti and spiral ganglion neurons. Further, the N-terminal release from the GSDME mutant in HEI-OC1 cells caused pyroptosis, characterized by cell swelling and rupture of the plasma membrane, releasing lactate dehydrogenase and cytokines such as interleukin-1β. We also observed that the N-terminal release from GSDME mutants could permeabilize the mitochondrial membrane, releasing cytochromes and activating the mitochondrial apoptotic pathway, thereby generating possible positive feedback on the cleavage of GSDME. Furthermore, we found that treatment with disulfiram or dimethyl fumarate might inhibit pyroptosis and apoptosis by inhibiting the release of GSDME-N from GSDME mutants. In conclusion, this study elucidated the molecular mechanism associated with hearing loss caused by GSDME gene mutations, offering novel insights for potential treatment strategies.

Effects of combined treatment with hydrogen-rich electrolyzed water and tea polyphenols on oxidative stress, intestinal injury and intestinal flora disruption in heat-stressed mice - Yao Zang; Beibei Zhang; Guosheng Zhang; Jie Hu; Dengqun Shu; Jiahong Han; Mengzhen Hu; Mingming Tu; Wenduo Qiao; Renxin Liu; Yitian Zang (Journal of Thermal Biology, 2024)

Gradual effects of gradient concentrations of perfluorooctane sulfonate on the antioxidant ability and gut microbiota of red claw crayfish (Cherax quadricarinatus) - Chenxi Zhu; Weiwei Lv; Shuang Hong; Mingming Han; Weiguo Song; Chengbin Liu; Chunxia Yao; Qichen Jiang (Science of The Total Environment, 2024)

Graph neural network-based topological relationships automatic identification of geological boundaries - Shuyang Han; Yichi Zhang; Jiajun Wang; Dawei Tong; Mingming Lyu (Computers & Geosciences, 2024)

Insights into the effects of 1,3-dioxolane on the growth of sI CO2 hydrate: A molecular dynamics simulation study - Yuanbo Wang; Han Jia; Guopeng Wu; Mingming Xu; Chuanqi Li; Xiyang Wang; Wenxin Cao; Ziwei Wei; Kaihe Lv; Dexin Liu; Pan Huang (Fuel, 2024)

Lightweight, ultra-broadband SiOC-based triply periodic minimal surface meta-structures for electromagnetic absorption - Junbin Lu; Mingming Sheng; Hongyu Gong; Jie Jing; Xiaobin Zhou; Jianqiang Bi; Weibin Zhang; Guifang Han; Zidong Zhang; Haoyu Fang; Yijie Zhou; Ke Bi (Chemical Engineering Journal, 2024)

Cotton-derived three-dimensional carbon fiber aerogel with hollow nanocapsules and ultrahigh adsorption efficiency in dynamic sewage treatment system - Peng Zhang; Lei Zhang; Xiaoyan Yang; Mingming Chi; Yue Han; Zehao Zhang; Changhua Liu; Wubo Wan; Xiaoming Zhao (Bioresource Technology, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Effects of different concentrations and particle sizes of nanoplastics on gut microbiology, metabolism, and immunity in Chiromantes dehaani - Mingming Han; Tian Zhu; Zihan Zhou; Qin Si; Chenxi Zhu; Yiming Li; Qichen Jiang (Fish & Shellfish Immunology, 2024)

MMF-CNN: a multimodal fusion CNN network for winter wheat extraction incorporating active and passive time series data - Jingyi Chen; Haifeng Han; Mingming Xu; Jianhua Wan; Shanwei Liu (International Journal of Remote Sensing, 2024)

Utilizing residual networks for remote sensing estimation of total nitrogen concentration in Shandong offshore areas - Hongxia Zheng; Yulin Wu; Haifeng Han; Juan Wang; Shanwei Liu; Mingming Xu; Jianyong Cui; Muhammad Yasir (Frontiers in Marine Science, 2024)
Nitrogen is one of the critical factors in water pollution and eutrophication, so applying the deep learning method in remote sensing inversion of nitrogen can provide basic information for environmental management. This paper proposes a two-step feature extraction method to solve the problem that the number of bands in water quality inversion is insufficient and the deep learning method cannot be fully exploited. Firstly, manual feature extraction is completed through the fusion between bands to obtain a set of high-latitude shallow factors, which make the features rich and diverse. Then, a one-dimensional convolutional residual network (ResNet-1D) is constructed, and the deep features are automatically extracted through convolution operations of the model, where the residual learning is used to reduce the training difficulty. The full connection is established through depth features. The comparison of models shows that the Mean Relative Error (MRE) is decreased by at least 10% in both test and validation datasets. Finally, the spatiotemporal distribution of total nitrogen concentration (TNC) in the coastal waters of Shandong is explored. In general, the spatial distribution is that the concentration near the coast is higher than the far. The temporal variation is that the monthly mean of the TNC is low in March, moderate in May and August, and high in October; the annual average value of TNC is 0.3mg/L, which has decreased slightly year by year since 2014.

Characterization of the effects of Chinese peony (Radix paeoniae Alba) and its active ingredients on the hematopoietic function of the Chinese mitten crab (Eriocheir sinensis) - Sunjian Lyu; Weifeng Shen; Qi Guo; Mingming Han; Fulei Xiong; Li Liu; Weishao Bu; Julin Yuan; Bao Lou (Aquaculture, 2024)

Unraveling the threat: Microplastics and nano-plastics' impact on reproductive viability across ecosystems - Ji Liang; Feng Ji; Hong Wang; Tian Zhu; James Rubinstein; Richard Worthington; Anisah Lee Binti Abdullah; Yi Juin Tay; Chenxin Zhu; Andrew George; Yiming Li; Mingming Han (Science of The Total Environment, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

Detection and prediction of pathogenic microorganisms in aquaculture (Zhejiang Province, China) - Tong Zhao; Zhencai Shen; Ping Zhong; Hui Zou; Mingming Han (Environmental Science and Pollution Research, 2024)

Comparative analysis of whole-transcriptome RNA expression of lung tissue of Chinese soft-shell turtle infected by Trionyx sinensis Hemorrhagic Syndrome Virus - Sunjian Lyu; Qi Guo; Weifeng Shen; Mingming Han; Fulei Xiong; Xiaoling Dai; Li Liu; Weishao Bu; Bao Lou; Julin Yuan (Fish & Shellfish Immunology, 2024)

Mass spectrometry analysis of intact protein N-glycosylation signatures of cells and sera in pancreatic adenocarcinomas - Mingming Xu; Zhaoliang Liu; Wenhua Hu; Ying Han; Zhen Wu; Sufeng Chen; Peng Xia; Jing Du; Xumin Zhang; Piliang Hao; Jun Xia; Shuang Yang (Journal of Zhejiang University-SCIENCE B, 2024)

Transcriptomic analysis following polystyrene nanoplastic stress in the Pacific white shrimp, Litopenaeus vannamei - Chenxi Zhu; Guoxing Liu; Anisah Lee Binti Abdullah; Mingming Han; Qichen Jiang; Yiming Li (Fish & Shellfish Immunology, 2023)

Effect of damming on hydrogeochemical characteristics and potential environmental risks in a large reservoir: Insights from different vertical layer sampling - Di Wang; Guilin Han; Mingming Hu; Yuchun Wang; Jinke Liu; Xi Gao (Environmental Research, 2023)

The organism fate of inland freshwater system under micro-/nano-plastic pollution: A review of past decade - Ji Liang; Sen Xiong; Chunlin He; Zhaobin Song; Song Yang; Daiqiang Ma; Wenchu Yan; Hong Wang; Rabia Tahir; Mingming Han (Aquatic Toxicology, 2023)

Baicalin alleviates bleomycin-induced early pulmonary fibrosis in mice via the mitoKATP signaling pathway - Mingming Han; Shayan Wang; Xuehua Zhou; Pengfei Zhang; Zhengyuan Han; Yang Chen; Haijian Cai; Lina Wu; Xiaoying Huang; Liangxing Wang; Yanfan Chen (Toxicology, 2023)

Change in energy-consuming strategy, nucleolar metabolism and physical defense in Macrobrachium rosenbergii after acute and chronic polystyrene nanoparticles exposure - Ji Liang; Anisah Lee Binti Abdullah; Hong Wang; Guoxing Liu; Mingming Han (Aquatic Toxicology, 2023)

Dietary polystyrene nanoplastics exposure alters hepatic glycolipid metabolism, triggering inflammatory responses and apoptosis in Monopterus albus - Chenxi Zhu; Wenzong Zhou; Mingming Han; Ying Yang; Yiming Li; Qichen Jiang; Weiwei Lv (Science of The Total Environment, 2023)

Spatial variation of surface erosion rate in a fault zone and its controlling factors - Xuemei Li; Huiping Zhang; Xiaoqing Chen; Weiming Liu; Mingming Han; Xudong Zhao (Geomorphology, 2023)

The effects of a polystyrene nanoplastic on the immune response and gut microbiota of Eriocheir sinensis and its post-recovery state - Mingming Han; Chenxi Zhu; Shengkai Tang; Ji Liang; Daming Li; YanXia Guo; Zakaria Zuraini; Qin Si; Qichen Jiang (Aquatic Toxicology, 2023)

Measuring the route topography impact on real driving emissions based on neural network models - Hualong Xu; Li Zhang; Hong Chang; Jinlin Han; Dongmei Wu; Xiangkun Gong; Mingming Fu (Environmental Research, 2023)

Ultrasound-induced cell disintegration and its ultrastructure characterization for the valorisation of Chlorella pyrenoidosa protein - Yong Deng; Xiaoling Yang; Tianyi Yan; Weidong Xu; Jiaheng Li; Ruihao Niu; Runan Zhao; Han Wang; Hao Wang; Tingting Chen; Mingming Guo; Wenjun Wang; et al. (Bioresource Technology, 2023)

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Neural spline flow multi-constraint NURBS method for three-dimensional automatic geological modeling with multiple constraints - Mingming Lyu; Bingyu Ren; Xiaoling Wang; Jiajun Wang; Jia Yu; Shuyang Han (Computational Geosciences, 2023)

Indoor air particles in research vessel from Shanghai to Antarctic: Characteristics, influencing factors, and potential controlling pathway - Xudong Wu; Fange Yue; Jiancheng Wang; Xiawei Yu; Hongwei Liu; Weihua Gu; Mingming Han; Juan Li; Zhouqing Xie (Journal of Environmental Sciences, 2023)

Structural characterization and anti-inflammatory effects of an arabinan isolated from Rehmannia glutinosa Libosch. - Han Zhang; Yimin Yue; Qian Zhang; Lanyuan Liang; Chuanqiu Li; Ying Chen; Wei Li; Mingming Peng; Mengru Yang; Mantong Zhao; Xia Cao; Luyang Zhong; et al. (Carbohydrate Polymers, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

Tidal currents in the coastal waters east of Hainan Island in winter - Min Li; Lingling Xie; Xiaolong Zong; Junyi Li; Mingming Li; Tong Yan; Ronglei Han (Journal of Oceanology and Limnology, 2022)

Molecular Characterization of Prdx Family and Response of Antioxidant Enzymes in Berberine Hydrochloride-Treated Charybdis japonica Infected With Aeromonas hydrophila - Mingming Han; Tianheng Gao; Yuxin Liu; Zakaria Zuraini; Chenxi Zhu; Tongqing Zhang; Feng Ji; Qichen Jiang; Xian Sun (Frontiers in Marine Science, 2021)
Berberine hydrochloride is an isoquinoline alkaloid, which has antitumoral, antibacterial, and antiviral activities in vivo and in vitro . Charybdis japonica is one of the main economic species of crab in Southeast Asia. We studied the molecular mechanism of oxidative stress in berberine hydrochloride-treated C. japonica infected with Aeromonas hydrophila . C. japonica were infected with A. hydrophila after being submerged in different concentrations (0, 100, 200, and 300 mg/L) of berberine hydrochloride for 48 h. The full-length cDNA of Prx6 and the ORFs of Prx5 and PXL2A were cloned. Prx6 and PXL2A each have one conserved domain, Cys44 , and Cys81 . The Prx5 conserved domain contains three important Cys loci, Cys75 , Cys100 , and Cys76 . Prx6 was different from Prx5 and PXL2A in the Peroxiredoxin family. The transcription levels of PXL2A infected with A. hydrophila were all higher than the control. The transcription levels of C. japonica were further increased by adding berberine hydrochloride and were increased the highest at a concentration of 300 mg/L. The activities of glutathione peroxidase, superoxide dismutase, and catalase in the hepatopancreas of berberine hydrochloride-treated C. japonica infected with A. hydrophila were significantly increased compared with those only infected with A. hydrophila and the control group. The glutathione transferase activity in the hepatopancreas was significantly increased in berberine hydrochloride-treated C. japonica . The results of this study provide a new understanding of the potential role of berberine hydrochloride on the oxidative stress mechanisms of C. japonica .

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Effect of Berberine Hydrochloride Treatment on Transcriptomic Response in Gill Tissue of Charybdis japonica Infected With Aeromonas hydrophila - Mingming Han; Yuxin Liu; Tongqing Zhang; Daming Li; Qichen Jiang; Zakaria Zuraini (Frontiers in Marine Science, 2021)
Berberine hydrochloride is the main active ingredient of Coptis chinensis, which has demonstrated significant antibacterial activity against bacteria. However, the molecular mechanism underlying its effects is unclear in crabs. In this study, we used transcriptome sequencing to investigate the molecules involved in the therapeutic and defensive responses of Charybdis japonica infected with 10 5 colony-forming units (CFU)/L of Aeromonas hydrophila following treatment with berberine hydrochloride. A total of 5,409 differentially expressed genes were observed after exposure of C. japonicus for 72 h to 100 mg/L berberine hydrochloride, 100 mg/L berberine hydrochloride plus injection of 10 5 CFU/L A. hydrophila , and a control group injected with equal amount of physiological saline solution. Enrichment analysis revealed that these genes were involved in metabolism, cellular processes, signal transduction, and immune function. The transcriptomic results indicated that exposure to berberine hydrochloride activated glutathione metabolism, oxidative phosphorylation, fatty acid degradation, retinol metabolism, pyruvate metabolism, and the hypoxia-inducible factor 1 signaling pathway. Transcriptomic analysis and relative mRNA level analysis also identified acid hydrolase genes and phagosomal genes as key factors regulating the adaptation of acid berberine-infused C. japonicus to infection with A. hydrophila , Based on the ability of berberine hydrochloride to induce acid hydrolase and phagosomal gene expression, which can in turn remove bacteria, immersion in berberine hydrochloride may remove A. hydrophila and thus improve the survival of C. japonica . The results of this study provided a new scientific basis for the potential role of berberine hydrochloride in the immune mechanisms of crabs.

Characterization of EGR-1 Expression in the Auditory Cortex Following Kanamycin-Induced Hearing Loss in Mice - Man Wang; Yuechen Han; Xue Wang; Shuo Liang; Chuan Bo; Zhenbiao Zhang; Mingming Wang; Lei Xu; Daogong Zhang; Wenwen Liu; Haibo Wang (Journal of Molecular Neuroscience, 2021)

Correction to: TAK1 is involved in sodium L‑lactate‑stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

TAK1 is involved in sodium L-lactate-stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Association between selected urinary heavy metals and asthma in adults: a retrospective cross-sectional study of the US National Health and Nutrition Examination Survey - Xiuzhu Li; Yun Fan; Yan Zhang; Xiaomin Huang; Zhenyao Huang; Mingming Yu; Qiaoqiao Xu; Xiumei Han; Chuncheng Lu; Xinru Wang (Environmental Science and Pollution Research, 2021)

The impact of global dimming on crop yields is determined by the source–sink imbalance of carbon during grain filling - Liping Shao; Zijuan Liu; Haozheng Li; Yaling Zhang; Mingming Dong; Xuanhe Guo; Han Zhang; Baowei Huang; Rongbing Ni; Gang Li; Chuang Cai; Weiping Chen; et al. (Global Change Biology, 2021)
Global dimming reduces incident global radiation but increases the fraction of diffuse radiation, and thus affects crop yields; however, the underlying mechanisms of such an effect have not been revealed. We hypothesized that crop source–sink imbalance of either carbon (C) or nitrogen (N) during grain filling is a key factor underlying the effect of global dimming on yields. We presented a practical framework to assess both C and N source–sink relationships, using data of biomass and N accumulation from periodical sampling conducted in field experiments for wheat and rice from 2013 to 2016. We found a fertilization effect of the increased diffuse radiation fraction under global dimming, which alleviated the negative impact of decreased global radiation on source supply and sink growth, but the source supply and sink growth were still decreased by dimming, for both C and N. In wheat, the C source supply decreased more than the C sink demand, and as a result, crops remobilized more pre‐heading C reserves, in response to dimming. However, these responses were converse in rice, which presumably stemmed from the more increment in radiation use efficiency and the more limited sink size in rice than wheat. The global dimming affected source supply and sink growth of C more significantly than that of N. Therefore, yields in both crops were dependent more on the source–sink imbalance of C than that of N during grain filling. Our revealed source–sink relationships, and their differences and similarities between wheat and rice, provide a basis for designing strategies to alleviate the impact of global dimming on crop productivity.

Replication study and meta-analysis indicate a suggestive association of RUNX3 locus with primary biliary cholangitis - Rohil Jawed; Mingming Zhang; Chan Wang; Shu-Han Yang; Peng Jiang; Qiuyuan Wu; Li Li; Weichang Chen; M. Eric Gershwin; Ye Tian; Michael F. Seldin; Xiong Ma; et al. (Immunogenetics, 2020)

Artemisinin suppresses hepatocellular carcinoma cell growth, migration and invasion by targeting cellular bioenergetics and Hippo-YAP signaling - Yujie Li; Jing Lu; Qin Chen; Shengnan Han; Hua Shao; Pingyi Chen; Qiumei Jin; Mingyue Yang; Fugen Shangguan; Mingming Fei; Lu Wang; Yongzhang Liu; et al. (Archives of Toxicology, 2019)

Visualization of Turbot (Scophthalmus maximus) Primordial Germ Cells in vivo Using Fluorescent Protein Mediated by the 3′ Untranslated Region of nanos3 or vasa Gene - Li Zhou; Xueying Wang; Qinghua Liu; Shihong Xu; Haixia Zhao; Mingming Han; Yunong Wang; Zongcheng Song; Jun Li (Marine Biotechnology, 2019)

New isolates from leaves of Nicotiana tabacum and their biological activities - Shanzhai Shang; Jianlian Shi; Jianguo Tang; Juxing Jiang; Wei Zhao; Xudong Zheng; Ping Lei; Jingmei Han; Chengya Wang; Dalin Yuan; Guangyu Yang; Yongkuan Chen; et al. (Natural Product Research, 2019)

A Three-Dimensional Culture System with Matrigel Promotes Purified Spiral Ganglion Neuron Survival and Function In Vitro - Wenqing Yan; Wenwen Liu; Jieyu Qi; Qiaojun Fang; Zhaomin Fan; Gaoying Sun; Yuechen Han; Daogong Zhang; Lei Xu; Mingming Wang; Jianfeng Li; Fangyi Chen; et al. (Molecular Neurobiology, 2018)

Hydrological response and thermal effect of karst springs linked to aquifer geometry and recharge processes - Mingming Luo; Zhihua Chen; Hong Zhou; Liang Zhang; Zhaofeng Han (Hydrogeology Journal, 2018)

Altered expression of the TaRSL2 gene contributed to variation in root hair length during allopolyploid wheat evolution - Haiming Han; Huifang Wang; Yao Han; Zhaorong Hu; Mingming Xin; Huiru Peng; Yingyin Yao; Qixin Sun; Zhongfu Ni (Planta, 2017)

Dynamics and anthropogenic impacts of multiple karst flow systems in a mountainous area of South China - Mingming Luo; Zhihua Chen; Robert E. Criss; Hong Zhou; He Huang; Zhaofeng Han; Tingting Shi (Hydrogeology Journal, 2016)

Oxidants and anti-oxidants in turbot seminal plasma and their effects on sperm quality - Mingming Han; Fuhong Ding; Zhen Meng; Jilin Lei (Journal of Ocean University of China, 2015)

Determination and analysis of the dissipation and residue of cyprodinil and fludioxonil in grape and soil using a modified QuEChERS method - Wen Zhang; Hongyu Chen; Xinwei Han; Zaihui Yang; Mingming Tang; Jing Zhang; Song Zeng; Deyu Hu; Kankan Zhang (Environmental Monitoring and Assessment, 2015)

In vitro and in vivo protection against enterovirus 71 by an antisense phosphorothioate oligonucleotide - Juan Liu; Zhe Zhou; Kang Li; Mingming Han; Jing Yang; Shengqi Wang (Archives of Virology, 2014)

Study on polymerization effect of polyembryony genes by SSCP marker and family trees in Chinese goats - Guang Li; Xiaopeng An; Jinxing Hou; Ling Li; Dan Han; Mingming Yang; Yana Wang; Guangqin Zhu; Jiangang Wang; Yuxuan Song; Bin Yun Cao (Molecular Biology Reports, 2011)

Identification of QTL underlying soluble pigment content in soybean stems related to resistance to soybean white mold (Sclerotinia sclerotiorum) - Dongmei Li; Mingming Sun; Yingpeng Han; Weili Teng; Wenbin Li (Euphytica, 2010)

Protective effect of puerarin on diabetic retinopathy in rats - Yan Teng; Hao Cui; Mingming Yang; Han Song; Qingsheng Zhang; Ying Su; Jianqiu Zheng (Molecular Biology Reports, 2009)